2020
DOI: 10.1021/acsanm.0c01104
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Laser-Thinning of MoS2 Nanolayers and Transformation to Amorphous MoOx for 2D Monolayer Fabrication

Abstract: Laser-thinning of 2D materials such as MoS 2 is a promising approach for a local reduction of the number of multilayers down to a monolayer. For a precise control of the thinning process real-time monitoring is required. In this work, shortwavelength lasers emitting at 325 or 406 nm respectively are used for laser-thinning and simultaneous Raman or photoluminescence spectroscopy of MoS 2 . The time evolution of the Raman and photoluminescence bands during the process shows a layer-by-layer thinning of MoS 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Among various 2D nanomaterials whose graphene is the most well-known representative, 2D transition-metal oxides (TMO) and transition-metal dichalcogenides (TMD) are actively investigated. In particular, α-MoO 3 ( Pnma space group) is an n-type semiconductor with a wide experimental band gap of ∼3.2 eV, , while 2H-MoS 2 ( P 6 3 / mmc space group) exhibits an indirect band gap of ∼1.23 eV. , Although recent experimental , and theoretical works ,, highlight the possible synthesis and key interests of MoO 3 /MoS 2 heterostructures for various applications, it remains unknown to which extent the optoelectronic properties of such 2D heterostructure can be optimized to match the requirements of photocatalytic materials. DFT with hybrid functional study demonstrated that the MoO 3 /MoS 2 heterostructure is a type III heterojunction, being a good candidate for a tunnel field-effect transistor (TFET)-type device , but not for photocatalytic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Among various 2D nanomaterials whose graphene is the most well-known representative, 2D transition-metal oxides (TMO) and transition-metal dichalcogenides (TMD) are actively investigated. In particular, α-MoO 3 ( Pnma space group) is an n-type semiconductor with a wide experimental band gap of ∼3.2 eV, , while 2H-MoS 2 ( P 6 3 / mmc space group) exhibits an indirect band gap of ∼1.23 eV. , Although recent experimental , and theoretical works ,, highlight the possible synthesis and key interests of MoO 3 /MoS 2 heterostructures for various applications, it remains unknown to which extent the optoelectronic properties of such 2D heterostructure can be optimized to match the requirements of photocatalytic materials. DFT with hybrid functional study demonstrated that the MoO 3 /MoS 2 heterostructure is a type III heterojunction, being a good candidate for a tunnel field-effect transistor (TFET)-type device , but not for photocatalytic materials.…”
Section: Introductionmentioning
confidence: 99%
“…This scenario requires more study, but it would be a plausible explanation for the strong PL intensity from the bilayer MoS 2 . Another probable scenario to explain our observations would be etching the top layer and thinning it to a ML of MoS 2 via UV irradiation, because a laserthinning process has been reported to reduce the thickness of MoS 2 [37][38][39]. However, the morphology and color of the sample are maintained in the process, as shown in Figure 5.…”
Section: Resultsmentioning
confidence: 94%
“…Despite the initial progress, the laser-induced ALE approach remained relatively undeveloped until 2018 when it found successful application in layer thinning of layered materials like MoS 2 and MoTe 2 due to their weak interlayer interaction (van der Waals forces). [19][20][21] However, the application of laser-induced ALE remains a challenge when it comes to bulk materials such as silicon (Si), which has tightly bound covalent bonds. In ALE of Si, chlorine (Cl) is typically used to weaken the Si-Si bonds prior to subsequent removal, forming SiCl as the primary product during modification on surfaces.…”
Section: Introductionmentioning
confidence: 99%